2019
DOI: 10.1016/j.jbankfin.2018.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Politicians’ promotion incentives and bank risk exposure in China

Abstract: This paper shows that politicians' pressure to climb the career ladder increases bank risk exposure in their region. Chinese local politicians are set growth targets in their region that are relative to each other. Growth is stimulated by debt-financed programs which are mainly financed via bank loans. The stronger the performance incentive the riskier the respective local bank exposure becomes. This effect holds primarily for local banks which are under a certain degree of control of local politicians and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Enterprises have limited influence in the legislative and regulatory processes, functioning primarily as policy executors. Politicians employ their authority to direct firms toward achieving political objectives, heightening their chances of promotion (Hao & Lu, 2018; Piotroski & Zhang, 2014; Wang et al, 2019; Yan & Chang, 2018; You et al, 2018; M. Zhang et al, 2016). SOEs assume a significant role for serving political interests at the expense of financial performance (Bai et al, 2006; Fan et al, 2013).…”
Section: Institutional Background and Research Hypothesesmentioning
confidence: 99%
“…Enterprises have limited influence in the legislative and regulatory processes, functioning primarily as policy executors. Politicians employ their authority to direct firms toward achieving political objectives, heightening their chances of promotion (Hao & Lu, 2018; Piotroski & Zhang, 2014; Wang et al, 2019; Yan & Chang, 2018; You et al, 2018; M. Zhang et al, 2016). SOEs assume a significant role for serving political interests at the expense of financial performance (Bai et al, 2006; Fan et al, 2013).…”
Section: Institutional Background and Research Hypothesesmentioning
confidence: 99%
“…The central government manages local government officials through performance-related assessments to reduce agency costs [ 34 ]. Previous works in the literature found that official promotion incentive can promote local investment [ 47 ], increase credit expansion [ 48 ] and improve water pollution [ 49 ]. As poverty alleviation strategies are becoming more important, the Chinese government have begun to evaluate the effectiveness of local government officials in poverty alleviation.…”
Section: Institutional Background and Research Hypothesesmentioning
confidence: 99%
“…In France, corporate CEOs with political backgrounds help re-elect politicians in their districts by having higher job and plant creation rates [ 60 ]. In transition and developing economies, governments intervene in the investment allocation tendencies of firms, thereby achieving government objectives [ 61 ] or stimulating economic growth by intervening in bank loans to finance projects [ 48 ]. While these papers focus on political goals centered on GDP, this paper attempts to examine the pro-poor political goals of local government officials.…”
Section: Institutional Background and Research Hypothesesmentioning
confidence: 99%
“…Samples within the same category are defined as "comparable". The promotion pressures of local leaders will only come from the economic performances in regions within the comparable region (Fang et al 2018;Wang et al 2019). Next, we calculate the difference between the value of the budget surplus ratio, the unemployment rate, and the GDP growth rate in each city and their mean values within the comparable region (i.e., in cities within the same category).…”
Section: Promotion Pressuresmentioning
confidence: 99%